Experimental investigations on spray characteristics of non-edible oils using phase doppler particle analyser - Subramani, Sivakumar; Gajbhiye, Narendra Laxman; Murugesan, Venkatasudhahar; Mottaiyan, Prabhu; Dhairiyasamy, Ratchagaraja (Matéria, 2024)
ABSTRACT The study uses a phase Doppler particle analyzer to experimentally investigate the influence of minimum quantity lubrication (MQL) parameters on the spray characteristics of vegetable oils in the MQL system. Droplet velocity and diameter of the Azadirachta Indica, Ceiba Pentandra, Madhuca Longifolia, and Calophyllum Inophyllum are measured by varying pressure levels, flow rate, and nozzle diameter. MQL system, Spray chamber system, and PDPA unit are the major systems in the PDPA system. MQL system supplies the oil as a mist in the spray chamber through the nozzle. At the same time, the PDPA unit measures the spray characteristics of the disintegrated oil using the Doppler effect. The oil droplet’s size decreased when the pressure increased, whereas it increased with the oil’s viscosity. The nozzle of 2 mm diameter reduced the droplet size while it increased for the 2.5 mm nozzle. The effect of the oil flow rate on spray characteristics was found to be insignificant. The results showed that lower-viscosity oils, ideal for machining, offer less resistance to disintegration and generate smaller droplets in the spray. Among all, the disintegration of oils is highly encouraged by pressure and nozzle diameter. In addition, suitable MQL system parameters can be identified for sustainable machining.